PENGARUH INSTITUTIONAL DISTANCE TERHADAP TINGKAT KEPEMILIKAN EKUITAS DALAM AKUISISI LINTAS NEGARA OLEH PERUSAHAAN MULTINASIONAL TIONGKOK - Kevin Christoper (2022)
This research aims to determine the effect of institutional distance on the level of equity ownership. The sampling technique in this research used a purposive sampling technique. The sample of this research is cross-border acquisition transactions between Chinese multinational companies and target countries in the Southeast Asia region in the 2015 - 2019 period so the total sample of this research is 32 transactions. The analysis technique in this study is Multiple Linear Regression with the Ordinary Least Square (OLS) model. This study's results indicate that economic distance and geographical distance partially affect the level of equity ownership significantly. In contrast, the administrative distance does not partially affect the level of equity ownership of the target company by Chinese multinational companies.